2001, a space odyssey [videorecording (Blu-Ray)] - Kubrick, Stanley; Clarke, Arthur C. (Arthur Charles), 1917-2008; Dullea, Keir, 1936-; Lockwood, Gary, 1937-; Sylvester, William, 1922-1995 (Warner Bros. Home Entertainment, 2018)
A space voyage to Jupiter erupts in disaster when the ship's computer goes mad.